PTH-195 Curos™ line caps are effective in reducing catheter related sepsis in inpatients receiving parenteral nutrition. (22nd June 2015) - Wheatley, DJ; Rowlands, S; Chapman, J; Menon, S; Steed, H; Kington, A; Uprichard, G; Robinson, K; Murugananthan, A
Abstract : Introduction: Catheter related sepsis (CRS) can result in disrupted feeding, parenteral nutrition (PN) waste, systemic sepsis, central vein thrombosis and potential prolonged hospital stay in inpatients receiving PN. Alcohol-impregnated disinfection caps reduce CRS in home PN patients 1 and hospital inpatients with indwelling central lines. 2 Their role in reduction of CRS in inpatients receiving PN is less clear. Method: Prospective data from inpatients receiving PN from April 2013 to January 2015 was assessed. CUROS TM line caps were introduced on 8/09/14 in addition to an existing standard aseptic non-touch technique for all patients receiving PN. Patients received PN via a peripherally inserted central catheter or a dedicated port of a central venous catheter. CRS were analysed in patients without and with the CUROS TM device and expressed as events/1000 catheter days. CRS was confirmed by a positive culture from blood withdrawn from the line or from line tip culture. Results: There were no differences in baseline characteristics between the 2 groups (Table 1 ). In the 17 months prior to the caps being used the incidence of line infections in patients receiving PN was 6.17/1000 line days. In the 5 months after their introduction this fell to 0.00/1000 line days (p-value 0.014) Conclusion: Upon introduction of a simple alcohol-impregnated disinfection cap there has been a significant fall in CRS rates related to PN. The cost to the Trust of a CUROS TM cap is £0.32 and further assessment of the cost saving to the Trust will be undertaken. Disclosure of interest: None Declared. References: Small M. The impact of 70% isopropyl alcohol port protection caps on catheter related bloodstream infection in patients on home parenteral nutrition. Poster, World Congress Vascular Access 2014 Merrill KC, Sumner S, Linford L, et al . Impact of universal disinfectant cap implementation on central line-associated bloodstream infections. American Journal of Infection Control 2014;42:1274–7